Febrile neutropenia: Median door-to-needle time – Results of an initial audit. (January 2015) - Ali, Natasha; Baqir, Muhammad; Hamid, Aasma; Khurshid, Mohammad
Abstract : Background: Recently, due to inadequacies during immediate management of patients with febrile neutropenia, a new gold standard 'door-to-needle' time of 1 hour for the administration of intravenous antibiotics was introduced. Objective: The aim of this audit was to identify whether that target was being met in our emergency department (ED). This is phase 1 of the study which will be followed by identification of barriers to the achievement of the target and recommendations for improvement. Materials and methods: Data were collected from January 2013 to April 2013 of consecutive patients (adult and pediatric age group) who presented to the ED with febrile neutropenia for various underlying causes. Fever was defined as single oral temperature of >38.3°C (101°F) or a temperature of >38.0°C (100.4°F) sustained for more than 1 hour. Neutropenia was defined as absolute neutrophil count <0.5 × 10 9 /l, or expected to fall below that number. Variables analyzed included age, gender, antibiotics administered, underlying diagnosis, day of presentation, and door-to-needle time. Results: During the study period, there were n  = 81 patients who presented with febrile neutropenia. There were n  = 49 were males and n  = 32 were females. There were n  = 37 patients in the pediatric age group while rest were adults. Patients most commonly had an underlying hematological malignancy ( n  = 49). A combination of piperacillin/tazobactam (4.5 g × Q8hrly) and amikacin (750 mg × once daily) was most frequently administered ( n  = 57) to these patients. The median door-to-needle time was 45 minutes (range ± SD: 10 minutes to 6 hours ± 1 hour 10 minutes). Long delays of over 4 hours occurred in n  = 4 patients (all were adults). There were minimal delays observed in pediatric patients due to 'red alert' policy implementation. Long delays occurred on weekdays and weekends, equally. Conclusion: The overall median door-to-needle time was 45 minutes, which was in the accepted range. However, delays that occurred demand improvements like introducing 'red alert' policy for adult patients, counseling of staff and residents, identifying potential barriers in achieving the target time along with solutions, and developing hospital-based guidelines on managing patients with neutropenic sepsis.